Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah, Dan Dana Alokasi Umum Terhadap Pengalokasian Anggaranbelanja Modal (studi pada pemerintah Kabupaten/Kota Se-Eks Karesidean Surakarta Tahun Anggaran 2011-2013) - Anugrah Wati, Tri, Drs. Eko Sugiyanto M.Si (2016)
This study aimed to analyze the effect of economic growth, regional revenue and general allocation funds towards capital expenditure budget allocation for local government district / City Ex Surakarta Fiscal Year 2011-2013. In this study, the sampling method used is saturated sample is the entire population of the research sample. Samples are obtained and can be used a number of 21 reports on realization of budget and the GDP per capita in the ex-residency Surakarta. Variable tested in this study is a capital expenditure, economic growth, revenue (PAD), and the general allocation fund (DAU). The analysis used in this research is descriptive statistics, classical ujiasumsi, multiple regression analysis, T-test and F test From these results it can be concluded that economic growth does not significantly influence capital expenditure budget allocation. While the PAD and DAU partial effect and significant capital expenditure budget allocation. Keywords: economic growth, revenue (PAD), the general allocation fund (DAU), the capital expenditure budget.